PAMAM dendrimers: blood-brain barrier transport and neuronal uptake after focal brain ischemia - Santos, Sofia D. (2019)
Drug delivery to the central nervous system is restricted by the blood-brain barrier (BBB). However, with the onset of stroke, the BBB becomes leaky, providing a window of opportunity to passively target the brain. Here, cationic poly(amido amine) (PAMAM) dendrimers of different generations were functionalized with poly(ethylene glycol) (PEG) to reduce cytotoxicity and prolong blood circulation half-life, aiming for a safe in vivo drug delivery system in a stroke scenario. Rhodamine B isothiocyanate (RITC) was covalently tethered to the dendrimer backbone and used as a small surrogate drug as well as for tracking purposes. The biocompatibility of PAMAM was markedly increased by PEGylation as a function of dendrimer generation and degree of functionalization. The PEGylated RITC-modified dendrimers did not affect the integrity of an in vitro BBB model. Additionally, the functionalized dendrimers remained safe when in contact with the bEnd.3 cells and rat primary astrocytes composing the in vitro BBB model after hypoxia induced by oxygen-glucose deprivation. Modification with PEG also decreased the interaction and uptake by endothelial cells of PAMAM, indicating that the transport across a leaky BBB due to focal brain ischemia would be facilitated. Next, the functionalized dendrimers were tested in contact with red blood cells showing no haemolysis for the PEGylated PAMAM, in contrast to the unmodified dendrimer. Interestingly, the PEG-modified dendrimers reduced blood clotting, which may be an added beneficial function in the context of stroke. The optimized PAMAM formulation was intravenously administered in mice after inducing permanent focal brain ischemia. Twenty-four hours after administration, dendrimers could be detected in the brain, including in neurons of the ischemic cortex. Our results suggest that the proposed formulation has the potential for becoming a successful delivery vector for therapeutic application to the injured brain after stroke reaching the ischemic neurons.